PERBANDINGAN PENGGUNAAN MODEL PEMBELAJARAN RECIPROCAL TEACHING DENGAN MODEL PEMBELAJARAN STAD DILIHAT DARI HASIL BELAJAR IPS - Kartona Asnosus Ferpin; Rusno Rusno; Naim Naim (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
This study aims to determine the differences in social studies learning outcomes between students who use the Reciprocal Teaching learning model and the STAD learning model) in class VII SMP 17 Malang. The research sample was taken from 2 classes from 8th grade VII of SMP Negeri 17 Malang totaling 68 students divided into two experimental classes I and experimental class II, the first class was taught using the Reciprocal Teaching learning model and the second class was taught using the STAD learning model. This type of research is Quasi Experiment with design. Data were analyzed using prerequisite test analysis techniques and hypothesis testing with the help of the SPSS 16.00 for windows program. The results of the calculation of the value of tcount 3.046 with Sig .003. by determining the table of t values ​​with the formula df (n-2). The value of df = 66, so that rtable = 1.6682. Based on a significance level of 5%, the rcount result was 3,046> rtable 1.6682. so it can be said that Ha was accepted and Ho was rejected. So based on the results of the analysis of the data it can be concluded that there was a significant difference in the use of the Reciplrocal Teaching learning model with the STAD learning model seen from the learning outcomes of Grade VII students of SMP Negeri 17 Malang.